Important fish and shrimp fry in the Philippines coastal waters identification, collection and handling. - Barinao, T.U.; Solis, N.B.; Villaver, W.R.; Villaluz, A.C. (Tigbauan, Iloilo, Philippines SEAFDEC Aquaculture Department, 1986)
Aquaculture Extension Manual No. 10
Keywords: Siganids; Seabass; Milkfish; Shrimp fry; Fish fry